The influence of digital well-being on students' entrepreneurial intentions at Makassar State University - Ridwan, Nurul Haeriyah (Journal of Management and Digital Business, 2026)
This study aims to examine the effect of digital well-being on students' intentions to become entrepreneurs. A quantitative survey design was applied to students enrolled in the Entrepreneurship Study Programme at Makassar State University. A sample of 242 respondents was selected using simple random sampling with a margin of error of 5%. Data were collected using a validated and reliable Likert scale questionnaire. Data analysis used simple linear regression to evaluate the direct influence of digital well-being on entrepreneurial intentions. The results showed that digital well-being had a positive and significant influence on entrepreneurial intentions. This study concludes that a higher level of digital well-being strengthens students' ability to manage technology productively, which in turn increases their readiness for entrepreneurship. Theoretically, this research contributes by integrating digital well-being into the framework of entrepreneurial intentions in higher education. Practically, it is recommended that universities incorporate digital well-being skills into the curriculum of entrepreneurship programmes as a strategic effort to strengthen students' capacity to form effective entrepreneurial intentions in the digital age.